2016
DOI: 10.7874/jao.2016.20.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Profile of Adult Persons with Auditory Neuropathy Spectrum Disorders

Abstract: Background and ObjectivesThe auditory profile of a large number of persons with late onset auditory neuropathy spectrum disorder (ANSD) is recently described in the Indian context. The purpose of study was 1) to profile data on routine audiological parameters, cortical evoked potentials, and temporal processing, 2) to analyze the benefit from hearing aids for persons with ANSD, and 3) to understand the association between benefit from hearing aids and auditory profile.Subjects and MethodsThirty-eight adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Yuvaraj and Mannarukrishnaiah [ 24 ] investigated aided improvement in speech identification in 38 individuals with late onset ANSD. Further, they estimated the relation between audiological findings (PTA, SIS, and temporal processing) and aided benefit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuvaraj and Mannarukrishnaiah [ 24 ] investigated aided improvement in speech identification in 38 individuals with late onset ANSD. Further, they estimated the relation between audiological findings (PTA, SIS, and temporal processing) and aided benefit.…”
Section: Resultsmentioning
confidence: 99%
“…However, the extent of aided improvement in majority of the clients is limited. Investigations by Mathai and Yathiraj [ 23 ] as well as Yuvaraj and Mannarukrishnaiah [ 24 ] showed aided improvement above 20%, whereas other studies have shown lesser aided improvement. Relatively higher aided improvement in a few participants was attributed to preserved neural synchrony.…”
Section: Discussionmentioning
confidence: 99%
“…In humans with sensorineural hearing loss, longer gap detection thresholds correlate with poorer speech perception (45-47). Our results show that gap-detection is diminished with synaptopathy and improved with supranormal IHC synapse density, thus supporting the notion that noise- and age-induced synaptopathy (3, 11, 15) contribute to the deficits in auditory processing seen in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reporting studies indicate that 10% to 20% of adult humans with normal audiometric thresholds have hearing difficulties (56)(57)(58)(59). Furthermore, humans with sensorineural hearing loss, particularly in the high frequencies, have longer gap-detection thresholds that correlate with poorer speech perception (60)(61)(62)(63)(64). It has been proposed that cochlear synaptopathy could contribute to this highly prevalent auditory dysfunction (3,11,15).…”
Section: Discussionmentioning
confidence: 99%
“…The temporal measurements of click-ABR, such as the latencies of featured peaks I, III and V, and the interpeak periods I–V, I–III and III–V, were identified by the trained experts and measured in the SmartEP system. The data of speech-ABR were transferred to a Brainstem toolbox [14-16] on MATLAB platform (MathWorks, Natick, MA, USA) which is increasingly used in the customized analysis of ABR research [26] for further analysis. The automated peak-picking algorithm in the toolbox was used to detect all peaks objectively for a higher confidence.…”
Section: Methodsmentioning
confidence: 99%